"Departure of children from Barcelona, Ministry of Education (dining room), to Sitges" (children's colonie). Antich(center). Copied from CNT collection
"Departure of children from Barcelona, Ministry of Education (dining room), to Sitges" (children's colonie). Antich(center). Copied from CNT collection.